2021
DOI: 10.1684/epd.2021.1270
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of EEG training curricula for non‐specialist clinicians: a systematic qualitative review

Abstract: Objective. Neurologists and epileptologists are scarce in sub-Saharan Africa (SSA). Whilst electroencephalograms (EEGs) are becoming more available in the region, interpretation is typically undertaken by non-specialist clinicians with limited or no training. This is a systematic review of the peer-reviewed literature on EEG training of non-specialist clinicians worldwide, assessing the efficacy of the training methodology and the curricula content. Methods. The published literature was searched for papers rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The reason for this inaction is unclear and may pertain to a cognitive bias or lack of awareness, from the ordering practitioner, to analyse the report in sufficient detail. 15 It may also represent a lack of understanding of the current approach to the treatment of AF, in patients being investigated for altered consciousness, which was one of the principle reasons for ordering the EEG. 16 No long term follow up was available for these patients to determine if any adverse events resulted.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this inaction is unclear and may pertain to a cognitive bias or lack of awareness, from the ordering practitioner, to analyse the report in sufficient detail. 15 It may also represent a lack of understanding of the current approach to the treatment of AF, in patients being investigated for altered consciousness, which was one of the principle reasons for ordering the EEG. 16 No long term follow up was available for these patients to determine if any adverse events resulted.…”
Section: Discussionmentioning
confidence: 99%
“…More training needs to be provided to nonspecialist clinicians in order to improve access to safe and accurate EEG interpretation in LMIC. 49 Some learning initiatives have already been launched in LMIC to improve pediatric EEG training. For instance, the Global Organization of Health Education 50 offers face-to-face teaching and online teaching resources in sub-Saharan African countries, such as Ethiopia and Nigeria.…”
Section: Electroencephalographic Study Modalitiesmentioning
confidence: 99%
“…In 2021, a systematic review was performed on EEG tools for the non-specialist and found that whilst available, they are rarely critiqued for quality of impact [ 4 ]. The study found similarities with key concepts taught and that paediatric EEG training was not adequately addressed in some EEG training programs.…”
Section: Introductionmentioning
confidence: 99%